2021
DOI: 10.3390/en14102920
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Electric Vehicle Uptake by Updating Public Policies to Shift Attitudes and Perceptions: Case Study of New Zealand

Abstract: Actions to reduce greenhouse gas emissions are required from all actors. Adopting plug-in electric vehicles (EV) would reduce light motor vehicle travel emissions, a significant and rising emissions source. To encourage EV uptake, many governments have implemented policies which may be less effective than desired. Using New Zealand as a case study, we surveyed private motorists. The results show that consumers are heterogeneous, with varying car-buying motivations, perceptions, attitudes to EVs and awareness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Secondly, the adequate availability of a network of public recharging points (Mersky et al, 2016) is important to encourage consumer adoption of EVs. Furthermore, both these factors affect consumer attitudes, perceptions and willingness to adopt EVs (Broadbent et al, 2021;Haustein and Jensen, 2018). Likewise, Rietmann and Lieven (2019) found a direct link between government incentives and EV market share, especially for monetary measures and infrastructure supply, although other soft incentives such as access to bus lanes can be attractive (as it saves time, a factor that some individuals equate to monetary value).…”
Section: Key Barriers To Innovation and Bev Uptake And The Australian...mentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the adequate availability of a network of public recharging points (Mersky et al, 2016) is important to encourage consumer adoption of EVs. Furthermore, both these factors affect consumer attitudes, perceptions and willingness to adopt EVs (Broadbent et al, 2021;Haustein and Jensen, 2018). Likewise, Rietmann and Lieven (2019) found a direct link between government incentives and EV market share, especially for monetary measures and infrastructure supply, although other soft incentives such as access to bus lanes can be attractive (as it saves time, a factor that some individuals equate to monetary value).…”
Section: Key Barriers To Innovation and Bev Uptake And The Australian...mentioning
confidence: 99%
“…Many researchers have analysed availability, accessibility and profitability of public rechargers, investigated links to EV sales and related policies to consumer behaviour e.g. (Baumgarte et al, 2021;Broadbent et al, 2021;Chamberlain and Al Majeed, 2021;Falchetta and Noussan, 2021;Hardman and Tal, 2021;Bräunl et al, 2020;Illmann and Kluge, 2020;Wee et al, 2020;Patt et al, 2019;Figenbaum, 2018;Egnér and Trosvik, 2018;Levinson and West, 2018;Narassimhan and Johnson, 2018;Gnann et al, 2018;Cherchi, 2017;Jansson et al, 2017;Neaimeh et al, 2017;Pettifor et al, 2017;Figenbaum and Kolbenstvedt, 2016;Morrissey et al, 2016).…”
Section: Impact Of Availability Of Public Rechargersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, it is important to evaluate the impact each policy has on EV diffusion, considering the socioeconomic aspects of the area [33][34][35]. Studying this mechanism is essential to comprehend which policies are the most efficient and, thus, direct investments to increase EV sales, especially in countries where EV penetration is low, such as Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…), the need to study consumer preferences in vehicle purchase decisions is vital (Wangsness et al, 2020). In addition, Broadbent et al, (2021) associated purchasing behavior with individuals' capabilities like; knowledge & skills, consumer attitude, social status, and financial resources. Authors also identified that government policies, vehicle characteristics, consumer attitude, perceptions and symbolism of vehicles, marketing, and innovation adoption process are influential factors in shifting consumers preferences from conventional vehicles to green vehicles.…”
Section: Introductionmentioning
confidence: 99%